Pengaruh Brand Image dan Brand Trust terhadap Loyalitas Pelanggan pada Shopee dengan Kepuasan Pelanggan Sebagai Variabel Intervening - Calvin Feliks Cantona; Meilisa Alvita (BADAN PENERBIT STIEPARI PRESS, 2024)
Global e-commerce expansion, including in Indonesia, shows rapid growth, but there are disparities between e-commerce brands. Shopee leads in monthly visitors, Brand Used Most Often (BUMO), Share of Order (SOO), transaction value, and Top of Mind. This research examines the correlation of Shopee dimensions such as Brand Image, Brand Trust, Customer Satisfaction and Customer Loyalty using SEM-PLS with SmartPLS 4, involving 103 respondents. The results show: 1) Brand Image has a significant positive effect on Customer Satisfaction. 2) Brand Image has no significant effect on Customer Loyalty. 3) Brand Trust has a significant positive effect on Customer Satisfaction. 4) Brand Trust has no significant effect on Customer Loyalty. 5) Customer Satisfaction has a significant and positive effect on Customer Loyalty. 6) Brand Image influences Consumer Loyalty indirectly through Customer Satisfaction. 7) Brand Trust has an indirect effect on Customer Loyalty through Customer Satisfaction.